TRPC6 regulates phenotypic switching of vascular smooth muscle cells through plasma membrane potential-dependent coupling with PTEN - Numaga-Tomita, Takuro (2019)
Fil: Numaga-Tomita, Takuro. National Institutes of Natural Sciences. National Institute for Physiological Sciences; Japón.